Palusita a new Brazilian Euliini genus (Lepidoptera Tortricidae) and its two species (Bollettino di zoologia agraria e bachicoltura, 2024)
Palusita, a new genus of the tribe Euliini and its two species (P.paulista Razowski & Becker, P. ochrans Razowski & Becker) are describedfrom Eastern and Centrai Brazil.
Keywords: Palusita; Lepidoptera; Tortricidae; Neotropical; new taxa